Sustainability as an Aid to the Interpretation of the Economic Scenario - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2023)
Is it possible that the principles of sustainability economy offer some more inspiration in our eternal attempt to look beyond the present time? This hypothesis certainly cannot be denied, because we must choose between a kind of development positive for nature and another kind forged instead by the human selfishness. Some help to stay in the right direction are the useful aid offered by nature (universal and constant laws in economics) and the curative character of natural interventions implemented when we derail from the correct path of constant growth. As saying that the irregularities of false development, starting with the conjuncture cycle and its companions (inflation and deflation), are a real protection from the danger of an irreparable fall of the economic mechanism and then of whole civilization. The fact remains certain that once off the path of constant development, the correction introduced precisely by the conjuncture cycle is certainly painful and somewhat complicated. Nevertheless, it offers some opportunities to find the way out of the imbalance. Thus, believing that long-term deflation can be overcome with ultra-Keynesian remedies means to suppose that we can control the economic cycle and its evolutions. But unfortunately, it does not work that way. And are equally unfounded the suppositions that see in speculation - which takes the financial market away from real values – a way to help the weak and depressed economy within a deflation scenario. Still on this subject, the choice of Central Banks to follow or anticipate - in the event of deflation - the drop-in interest rates down to zero or even below, should be limited by introducing a lower threshold that should not be exceeded when interest rates are falling. Because otherwise the excited speculation, so fueled, will lead us to a probable financial crisis. Instead, it is just an irregularity created by the abandonment of constant growth with minimal damage to nature. An irregularity on the development path that we have identified as the sub-world. On the other hand, we should not forget that the community or rather its majority is the only accredited counterpart of the forces of nature, so the close alliance between a good governance and the community is the key to maintaining or rediscovering the path of constant growth with minimal damage to nature.